Queijo Minas artesanal da microrregião da Serra da Canastra: caracterização sensorial e eletroquímica - Bemfeito, Raquel Martino (2016)
The study of the characteristics of artisanal Minas cheese produced in the microregion of Serra da Canastra, in Minas Gerais, Brazil, is of great importance, especially considering that it refers to a traditional product. Many factors can influence the characteristics of the product, given that the production of this cheese is associated with the livelihoods of the producers and culture of the producing regions. Thus, to add value, control the production, quality and geographical identity of the cheeses, and avoid fakes, this study aimed to conduct electrochemical and sensory characterization of the artisanal Minas cheese produced in the microregion of Serra da Canastra. We evaluated ten samples of artisanal Minas cheese, certified by the Agricultural Institute, with maturation period between 22 and 25 days. Temporal dominance of sensations (TDS) and sensory acceptance tests were performed to verify the attributes that provide product quality. The electrochemical impedance spectroscopy was also used to characterize the cheeses. We observed that the TDS sensory profile varies among the evaluated artisanal Minas cheeses from Serra da Canastra, however, all evaluated chesses had good acceptance. Moreover, it is possible to infer that creamy, soft, hard and firm are positive attributes for cheese texture and bitter, salty, acid and buttery taste guides the acceptance of the cheese. By using the Electrochemical Impedance Spectroscopy technique, we found that there is no uniformity or standardization among cheeses produced in the microregion of Serra da Canastra, but there are groups of producers that produces similar cheeses. In addition, the technique proved to be very promising and effective, being able to distinguish and group producers based on the similarity of electrical impedance of their cheeses. This study provides important information for product standardization and quality improvement, in addition to aiding the indications of origin process.